How Well Can We Estimate Pedersen Conductance From the THEMIS White‐Light All‐Sky Cameras?. Issue 4 (3rd April 2019) - Lam, M. M.; Freeman, M. P.; Jackman, C. M.; Rae, I. J.; Kalmoni, N. M. E.; Sandhu, J. K.; Forsyth, C.
Abstract: We show that a white‐light all‐sky imager can estimate Pedersen conductance with an uncertainty of 3 mho or 40%. Using a series of case studies over a wide range of geomagnetic activity, we compare estimates of Pedersen conductance from the backscatter spectrum of the Poker Flat Incoherent Scatter Radar with auroral intensities. We limit this comparison to an area bounding the radar measurements and within a limited area close to (but off) imager zenith. We confirm a linear relationship between conductance and the square root of auroral intensity predicted from a simple theoretical approximation. Hence, we extend a previous empirical result found for green‐line emissions to the case of white‐light off‐zenith emissions. The difference between the radar conductance and the best‐fit relationship has a mean of −0.76 ± 4.8 mho and a relative mean difference of 21% ± 78%. The uncertainties are reduced to −0.72 ± 3.3 mho and 0% ± 40% by averaging conductance over 10 min, which we attribute to the time that auroral features take to move across the imager field being greater than the 1‐min resolution of the radar data. Our results demonstrate and calibrate the use of Time History of Events and Macroscale Interactions during Substorms all‐sky imagers for estimating Pedersen conductance. This technique allows the extension of estimates of Pedersen conductance from Incoherent Scatter Radars to derive continental‐scale estimates on scales of ~1–10 min and ~100 km 2 . It thus complements estimates from low‐altitude satellites, satellite auroral imagers, and ground‐based magnetometers. Plain Language Summary: The Sun is a rotating magnetic plasma ball that releases energetic charged particles and magnetism in a "solar wind." Sometimes, this wind "shakes hands" with the Earth's magnetic field, allowing energy to be pumped into region near the Earth, stretching magnetic field lines like an elastic band. Much energy is released explosively in a "substorm" causing complex and brilliant auroral light displays about the size of a continent. This can be examined really well over several kilometers by radars on the ground. However, the radars cannot tell you what is happening for the whole substorm which is the size of a continent. It had been suggested that you can use a surface camera with a filter on it to estimate the part of the conductivity that tells us how much electric currents are heating the atmosphere. We asked whether the network of nonfiltered cameras stretching across North America could measure the conductivity as well as a radar can. We found they do half as well as the radar. This means we can use this camera network and its data archive to learn more about how much substorms heat up the atmosphere and how complicated and changeable this behavior is. Key Points: We use a white‐light all‐sky imager to estimate Pedersen conductance to within an uncertainty of 3 mho or 40% We relate Pedersen conductance to the optical intensity with a single parabolic relationship across a wide range of geomagnetic activity Our results enable the exploitation of white‐light camera networks to study continental‐scale phenomena such as substorms